2020
DOI: 10.1097/01.nep.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Deliberate Practice Debriefing During a Response to Rescue Patient Simulation With Undergraduate Nursing Students

Abstract: The purpose of this multisite, randomized, pretest/posttest quasi-experimental study was to compare student nurse competency, learning retention, and perceived student support after exposure to a deliberate practice debriefing versus standardized debriefing. Fifty undergraduate students participated in the complex response to rescue simulation. The intervention group had significantly higher total mean and three subscale scores on the competency tool than the comparison group, although differences in learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Benefits: Debriefing was found to be superior to no debriefing, [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119] but it was unclear whether 1 method of debriefing was superior over another. Improved retention of skills was reported with video-reviewed debriefing vs without.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits: Debriefing was found to be superior to no debriefing, [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119] but it was unclear whether 1 method of debriefing was superior over another. Improved retention of skills was reported with video-reviewed debriefing vs without.…”
Section: Discussionmentioning
confidence: 99%
“…Summary of the evidence: Of the 54 randomized and 10 observational studies reviewed, 19 studies focused on standard debriefing compared with other debriefing methods, [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119] 6 studies compared low-fidelity to high-fidelity simulation-based training, [120][121][122][123][124][125] and 7 studies compared simulation to other learning modalities. [126][127][128][129][130][131][132] Studies included healthcare professionals and students, residents and fellows, or mixed teams.…”
Section: Discussionmentioning
confidence: 99%
“…Universities are required to map their academic programs and services with the perceptions of students and parents' academic requirements (Parzych et al, 2021). The skill development and behavior management of students requires student support services from the universities (Aronson et al, 2021) in order to develop sustainable institution. Research found that there is an inverse relationship between perceived student support and the anxiety levels of students incorporating positive orientation by universities (Jin and Dewaele, 2018).…”
Section: Literature Review 21 Theoretical Underpinningsmentioning
confidence: 99%
“…Furthermore, in university learning system, an important aspect is that of facilitating a student support system. With respect to academic support, the perceived and actual student support with respect to a particular education system plays an instrumental role in a student's life (Aronson et al, 2021;Visser and Visser, 2000). During the current pandemic scenario, the online student support became a critical factor for the students in terms of reliability of services, technology support system, faculty support, student's learning retention and support from HEIs' administration (Tice et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation